Severity and nursing workload in patients critically ill with COVID-19 - Meneguin, Silmara [UNESP] (2022)
Objective: to investigate the correlation between nursing workload and severity index in patients with COVID-19 in an Adult Intensive Care Unit. Method: this retrospective, cross-sectional study was conducted between February and October 2020, with data from 93 patients with COVID-19. Severity analysis was performed according to the Acute Physiology Age and Chronic Health Evaluation method and workload, by the Nursing Activities Score. Results: patients were predominantly elderly, male, with one or more comorbidities, and hospitalized for more than seven days. The average Nursing Activities Score at admission was 74.2 and the severity index was 24.47, with 66.6% lethality. Significant correlation was found between workload and patient severity (0.5132; p<0.0001). Conclusion: nursing workload correlated moderately with severity of patients with COVID-19. The study findings can help in scaling nursing staffs and preventing adverse events.